2022
DOI: 10.1002/aet2.10827
|View full text |Cite
|
Sign up to set email alerts
|

“Faces on a screen”: A qualitative study of the virtual and in‐person conference experience

Abstract: Introduction:The strengths and weaknesses of virtual and in-person formats within continuing professional development (CPD) are incompletely understood. This study sought to explore attendees' perspectives across multiple specialties regarding benefits and limitations of conference formats and strategies for successful virtual and hybrid (i.e., in-person conferences with a virtual option) conferences.Methods: From December 2020 to January 2021, semistructured interviews were conducted with participants who att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“… 34 Previous qualitative assessments of virtual and hybrid professional development conferences have identified flexibility, accessibility, and useful incorporation of technology as major assets of a virtual conference format that can help offset other downsides. 35 Hybrid or virtual formats also have the potential to improve diversity, equity, and inclusion within the medical field by removing financial, physical, and temporal barriers for individuals with disabilities, caretaking responsibilities, and financial constraints. 4 , 34 Although hybrid and virtual formats have already been successfully used in several fields, including surgery, dermatovenereology, and rheumatology, they have unexplored potential for further optimization and utilization.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Previous qualitative assessments of virtual and hybrid professional development conferences have identified flexibility, accessibility, and useful incorporation of technology as major assets of a virtual conference format that can help offset other downsides. 35 Hybrid or virtual formats also have the potential to improve diversity, equity, and inclusion within the medical field by removing financial, physical, and temporal barriers for individuals with disabilities, caretaking responsibilities, and financial constraints. 4 , 34 Although hybrid and virtual formats have already been successfully used in several fields, including surgery, dermatovenereology, and rheumatology, they have unexplored potential for further optimization and utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars contend that the flexibility offered by virtual delivery has the potential to eliminate systemic barriers for equity-denied groups [ 29 , 32 ]. In particular, COVID-19 may have increased access to medical education content for women [ 29 ], parents of young children [ 33 ], individuals from remote communities [ 29 , 34 ], and international audiences [ 35 ] who may face barriers to in-person attendance. Conversely, we found that in certain instances, virtual delivery impeded clinicians’ ability to meaningfully engage in CPD, particularly for women and senior clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there remains a paucity of literature on the unique considerations associated with meaningful engagement during hybrid events. Preliminary research has begun to contribute to this gap, for example, Gottlieb et al [ 35 ] found that using multiple mediums can introduce challenges with synchrony that dilute the quality of experience for both in-person and virtual audiences. The authors suggest that enlisting technology specialists, creating opportunities for interactivity and engagement, and ensuring that content is appropriate for digital format are crucial to enhancing hybrid events.…”
Section: Discussionmentioning
confidence: 99%
“…Os congressos virtuais oferecem oportunidades flexíveis e acessíveis a diversos pesquisadores, permitindo uma maior inclusão e diversidade nas discussões ao superar barreiras econômicas, geográficas, sociais e de gênero (Gottlieb et al, 2022;Valenti et al, 2021). Na mesma linha, Stamelou et al (2021) afirmam que a inclusão é uma das grandes vantagens dos congressos online, possibilitando a participação de todos, desde pesquisadores com menos renda até pessoas com deficiência e até mesmo àqueles que não têm a possibilidade de viajar para o evento, fazendo assim com que o evento alcance mais pessoas e tenha maior impacto acadêmico.…”
Section: Congressos Acadêmicos Onlineunclassified
“…(Sarabipour et al, 2021, p. 2). Essa nova realidade, principalmente no entendimento dos pontos fortes e fracos dos eventos virtuais e presenciais, ainda é compreendida de forma incompleta (Gottlieb et al, 2022).…”
unclassified